Observation of B(0) --> D0pi(0) and B(0) -->D(*0)pi(0). - Coan, T; Gao, Y; Liu, F; Maravin, Y; Narsky, I; Stroynowski, R; Ye, J; Artuso, M; Boulahouache, C; Bukin, K; Dambasuren, E; Mountain, R; et al. (2002)
We have studied the color-suppressed hadronic decays of neutral B mesons into the final states D*0pi(0). Using 9.67 x 10(6) BB pairs collected with the CLEO detector, we observe the decays B( 0) --> D0pi(0) and B( 0) -->D(*0)pi(0) with the branching fractions BB( 0) -->D0pi(0)) = (2.74(+0.36)(-0.32) +/- 0.55)x10(-4) and BB( 0) -->D(*0)pi(0)) = (2.20(+0.59)(-0.52) +/- 0.79)x10(-4). The first error is statistical and the second systematic. The statistical significance of the D0pi(0) signal is 12.1sigma ( 5.9sigma for D(*0)pi(0)). Utilizing the B( 0) -->D*0)pi(0) branching fractions we determine the strong phases delta(I,D(*)) between isospin 1/2 and 3/2 amplitudes in the Dpi and D*pi final states to be cosdelta(I,D) = 0.89 +/-0.08 and cosdelta(I,D*) = 0.89 +/- 0.08, respectively.